(untitled) (The Research of Medical Science Review, 2025)
Background: The purpose of this study was to assess the prevalence of radiographic changes in the temporomandibular joint (TMJ) using plain X-rays in an adult population. The study also aimed to investigate the potential associations between TMJ osseous alterations and patient-related factors, including age, sex, dental status, and medical history. Methods: A total of 50 patients aged 20 to 79 years were evaluated using plain X-rays of the TMJ. Patients were categorized into three age groups. Radiographic assessments focused on identifying osseous changes in the TMJ, including condylar flattening, erosion, and osteophyte formation. Statistical analyses, including chi-squared tests and general estimating equations, were conducted to determine the prevalence of TMJ changes and their correlation with demographic and clinical factors. Results: Data were collected from 50 patients, with 30% in the 20-39 years age group, 40% in the 40-59 years group, and 30% in the 60-79 years group. The majority of participants were female (60%), and the mean age was 48.3 ± 16.2 years. Regarding BMI, 52% were classified as having a normal weight, 36% were overweight, and 12% were obese. Common symptoms reported included pain (80%), limited jaw movement (36%), and clicking (30%). Additionally, 80% of patients had no chronic illnesses, while 20% had conditions such as arthritis. Conclusions: TMJ osseous changes detected on plain X-rays are common and increase also with age, reflecting potential functional or degenerative processes. These findings highlight the need for clinicians to assess TMJ radiographs carefully, particularly in older adults, to identify possible degenerative changes or parafunctional habits that may contribute to joint alterations.